Forced migration, female labor force participation, and intra-household bargaining: does conflict empower women? (2011)
Civilian displacement is a common phenomenon in developing countries confronted with internal conflict. Persons who are forcefully displaced, besides being exposed to direct aggressions, face substantial income losses, and, as they migrate to cities, they usually end up joining the informal labor force. This paper examines the consequences of forced displacement on female labor participation, and its subsequent impact on bargaining power and domestic violence. Our results show that women from forcefully displaced households are more likely to be employed, work longer hours, earn higher wages, and contribute in larger proportions to household earnings relative to rural women who remain in rural areas. However, as measured by several indicators, their greater contribution to households' earnings does not strengthen their bargaining power. Most notably, domestic violence does not appear to change as a response to larger contributions to household expenses. Because the children of displaced families have been the direct victims of conflict and domestic violence, the intra-generational transmission of violence is highly likely.